A Survey on Physician Perspectives and Treatment Preferences for Febrile Seizures in Children - C. Tulasi Priya; Chaudhary Devanand Gulab (Medical Research and Its Applications Vol. 9, 2024)
Background: Febrile seizures are the most common symptoms observed in pediatric patients and often prompt parents to seek medical attention. There are two types of febrile seizures: simple and Complex. While simple febrile seizures are typically harmless, complex febrile seizures can have long-term effects. These seizures occur due to fever without any intracranial infection or acute electrolyte imbalance between the ages of 6 months and 6 years old. Most children with febrile seizures experience normal growth patterns and development after an episode. However, evidence suggests that both parents and physicians hold misconceptions about managing fever effectively. Objective: This study aims to determine physician opinions regarding treatment preferences for children experiencing febrile seizure episodes within the age group ranging from six months up to five years old. Methods: In June-July 2021 we conducted a cross-sectional study involving primary care physicians (n=100). A self-administered questionnaire was used via a Google form survey to gather data. Descriptive statistics were employed for analysis. Results: Our study revealed that only 10% of physicians correctly identified a body temperature above 37.2°C as fever when measured axillary temperature is taken into account. Furthermore, just 26.2% of the surveyed physicians considered signs and symptoms other than fever before prescribing antipyretics. Notably, 85% of respondents prescribed antipyretics with the aim of controlling or preventing complications associated with fevers, particularly febrile seizures. Additionally, most participants (76.3%) indicated that high fever could be an indicator of severe bacterial infection Interestingly, the majority (91.3%) advised parents to alternate between ibuprofen and paracetamol if the child’s fever did not subside. Conclusion: Misconceptions regarding management and potential complications related to febrile seizures were evident among participating physicians in this study. The findings indicate a need for improved recognition, assessment, and management by primary care providers when it comes to managing underlying illnesses in children presenting with a fever-related condition.